Vibrio fischeri: Laboratory Cultivation, Storage, and Common Phenotypic Assays. Issue 1 (4th June 2020) - Christensen, David G.; Visick, Karen L.
Abstract: Vibrio fischeri is a nonpathogenic organism related to pathogenic Vibrio species that can be readily grown and stored with common laboratory equipment. In this article, protocols for routine growth, storage, and phenotypic assessment of V. fischeri, as well as recipes for useful media, are included. Specifically, this article describes procedures and considerations for growth of this microbe in complex and minimal media. It also describes assays for biofilm formation, motility, and bioluminescence, three commonly assessed phenotypes of V. fischeri . © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Growth of V. fischeri from frozen stocks Basic Protocol 2 : Growth of V. fischeri in rich, undefined liquid medium Alternate Protocol 1 : Growth of V. fischeri in minimal medium Basic Protocol 3 : Storage of V. fischeri in frozen stocks Basic Protocol 4 : Biofilm assay on solid agar Alternate Protocol 2 : Biofilm assay in shaking liquid culture Alternate Protocol 3 : Biofilm assay in static liquid culture Basic Protocol 5 : Motility assay Basic Protocol 6 : Luminescence assay